(untitled) (Andamios, Revista de Investigación Social, 2016)
This paper addresses the epistemological tensions generated due to the search for legitimization of scientific knowledge. It stems from the discussion about science seen through “nomothetic” and “ideographic” standpoints, coming to the conclusion that there is a tendency to theorize from a vision that comes from an organizational order, putting on the back burner, to a large extent, the legitimizer tension that occurs in the socialization of scientific knowledge. The paper also values possibilities to analyze social sciences from Bourdieu’s scientific field concept, who breaks up certain inertias about the official positions that theorize about science.